+0  
 
0
278
1
avatar

(-2x^3y^0z^3)^3

Guest Apr 20, 2017
 #1
avatar+556 
+3

I'm assuming your expression is this:

(-2x3y0z3)3

Let's get started.

-2= -8

(x3)3 = x9

y0 = 1, 13 = 1

(z3)3 = z9

Answer: -8x9z9

helperid1839321  Apr 21, 2017

33 Online Users

avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.